The Effect of Salinity on the Growth of Kappaphycus alvarezii (Jurnal Ilmiah PLATAX, 2025)
This study aims to determine the effect of different salinities on the growth of K. alvarezii.  This seaweed was obtained from Tumbak, Southeast Minahasa Regency—medium sea water for planting media in Malalayang water, Malalayang District, Manado City. The treatments were on salinity 25 ppt for the lower range, and 35 ppt for the higher range. The results showed that at a salinity of 25 ppt, a bacterial colony was obtained, whereas at a salinity of 35 ppt, only a stress condition was observed. The specific growth rate results for salinity levels of 25 and 35 ppt were significantly slower compared to the control treatment. The method used is algae cultivation in controlled containers, and bacterial isolation from seaweed thallus infected with ice-ice was carried out on SWC (Sea Water Complete) agar and TCBS (Thiosulphate Citrate Bile Salt) agar. This suggests that salinity is the key factor in seaweed growth. From the results, we can conclude that at salinities of 25 ppt and 35 ppt, the seaweed growth is not maximal because of bleaching.  This condition could be a trigger for the growth of bacteria in lower salinity (25 ppt).Key words: Kappaphycus alvarezii, salinity, bacteria, seaweed.